Evaluation of Human Interventions on Longshore Sediment Transport in Damietta Port Area - Ahmed Ibrahim; Anas El Molla; Hany Ahmed (Journal of Rehabilitation in Civil Engineering)
Coastal regions are increasingly vulnerable to climate change-induced hazards such as erosion, with the combination of environmental threats and human activities exacerbating the vulnerability of these ecosystems. The study, spanning eight decades (i.e. 1940-2020), utilizes ECMWF-ERA5 data and a high-resolution model (MIKE21 SM) to simulate Longshore Sediment Transport (LST) in response to human interventions. Model accuracy is validated against observed data from the Damietta buoy and 2011 bathymetry data. Additionally, comparisons with the estimated LST from previous regional studies confirm the model's reliability. The investigation focuses on identifying trends in LST before and after human interventions, including the construction of Damietta Port (DP) and subsequent coastal protection structures. Two different trend analysis methods, linear regression and Theil-Sen, are used to capture temporal variations in LST. According to Theil-Sen, trend values increased as a result of the port construction, with Gross LST (GLST) and Net LST (NLST) increasing by 100-160%, respectively. However, both GLST and NLST experienced significant decreases following coastal protection (i.e. 27-24%, respectively). Moreover, the correlation analysis of wave parameters and LST revealed a variety of relationships over periods, illustrating the complicated relationship between sediment transport processes and human activities. Notably, prior to the construction of DP, there were strong correlations between NLST, wave height, and peak wave period (i.e. R=0.81-0.79, respectively), but these decreased significantly after construction (i.e. R=0.59-0.60). Following coastal protection, correlations with sediment transport increased (i.e. R=0.79-0.77).